2018
DOI: 10.3390/su10124604
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-Temporal Changes of Soil Respiration across China and the Response to Land Cover and Climate Change

Abstract: Soil respiration (Rs) plays an important role in the carbon budget of terrestrial ecosystems. Quantifying the spatial and temporal variations in Rs in China at the regional scale helps improve our understanding of the variations in terrestrial carbon budgets that occur in response to global climate and environmental changes and potential future control measures. In this study, we used a regional-scale geostatistical model that incorporates gridded meteorological and pedologic data to evaluate the spatial Rs va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 53 publications
(82 reference statements)
0
5
0
Order By: Relevance
“…Various soil relevant factors and characteristics should be undertaken when analyzing relationship between soil respiration and influencing factors (Yan, Qin, Zhang, & Li, 2009). Wen et al (2018) analyzed the relationship between soil respiration and environmental factors and found that high soil respiration values may occur in areas that show a greater degree of synchronicity in the timing of their optimal temperature and moisture conditions. It was reported that soil respiration rate is affected by the interaction of soil moisture and soil temperature in the cropland and forest of Northwest China (Zhang et al, 2020).…”
Section: Interactive Effect Of Soil Temperature and Soil Water Content On Soil Respirationmentioning
confidence: 99%
“…Various soil relevant factors and characteristics should be undertaken when analyzing relationship between soil respiration and influencing factors (Yan, Qin, Zhang, & Li, 2009). Wen et al (2018) analyzed the relationship between soil respiration and environmental factors and found that high soil respiration values may occur in areas that show a greater degree of synchronicity in the timing of their optimal temperature and moisture conditions. It was reported that soil respiration rate is affected by the interaction of soil moisture and soil temperature in the cropland and forest of Northwest China (Zhang et al, 2020).…”
Section: Interactive Effect Of Soil Temperature and Soil Water Content On Soil Respirationmentioning
confidence: 99%
“…2015, Wen et al. 2018). However, the impact of any land‐use change is likely to show high spatial variability and will depend on topographical conditions, especially in areas with a complex terrain (Kang et al.…”
Section: Introductionmentioning
confidence: 98%
“…2015, Wen et al. 2018), but few have specifically identified the impact or role(s) that topography has. Therefore, the purposes of the study were as follows: (1) to examine how soil respiration responded to land‐use changes under different topographical conditions; (2) to quantify the interactive effects of multiple drivers on soil respiration in response to land‐use change under different topographical conditions; and (3) to identify the relative importance of the different drivers on soil respiration.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations